Molecular Pharming for low and middle income countries. (February 2020) - Murad, Sheeba; Fuller, Sebastian; Menary, Jonathan; Moore, Cathy; Pinneh, Elizabeth; Szeto, Tim; Hitzeroth, Inga; Freire, Marcos; Taychakhoonavudh, Suthira; Phoolcharoen, Waranyoo; Ma, Julian K-C
Abstract : Interest in applications and benefits that Molecular Pharming might offer to Low and Middle Income Countries has always been a potent driver for the research discipline, and a major reason why many scientists entered the field. Although enthusiasm remains high, the reality is that such a game-changing innovation would always take longer than traditional uptake of new technology in developed countries, and be complicated by external factors beyond technical feasibility. Excitingly, signs of increasing interest by LMICS in Molecular Pharming are now emerging. Here, three case studies from Thailand, South Africa and Brazil are used to identify some of the key issues when a new investment into Molecular Pharming manufacturing capacity is under consideration. At present, academic research is not necessarily addressing these issues. Only by understanding the concerns, can members of the academic community contribute to helping the development of Molecular Pharming for LMICs by focusing their research efforts appropriately.